2021
DOI: 10.1007/s00167-021-06660-2
|View full text |Cite
|
Sign up to set email alerts
|

Tibial slope, remnant preservation, and graft size are the most important factors affecting graft healing after ACL reconstruction

Abstract: Purpose The aim of this study was to determine the anatomic, operative and biological factors that inluenced graft healing after single-bundle anterior cruciate ligament (ACL) reconstruction. Methods One hundred fourteen consecutive patients who underwent anatomic single-bundle ACL reconstruction with quadrupled hamstring tendon autografts between 2016 and 2019 were retrospectively analyzed. Ninety-four patients met the inclusion criteria with minimum follow-up of 12 months. Patients were evaluated with multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Lower SNQ represents lower graft water content, more ligamentization, and better biomechanical properties ( 34 ). Remnant preservation is an independent associated factors of graft SNQ ( 35 ). Takahashi et al performed a retrospective analysis and showed that SNQ values of ACL grafted tendon at 2 years after surgery in ACLR-R Group were better than those in ACLR-S Group ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lower SNQ represents lower graft water content, more ligamentization, and better biomechanical properties ( 34 ). Remnant preservation is an independent associated factors of graft SNQ ( 35 ). Takahashi et al performed a retrospective analysis and showed that SNQ values of ACL grafted tendon at 2 years after surgery in ACLR-R Group were better than those in ACLR-S Group ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various demographic and radiological parameters have been reported to be predictive factors of SNQ values, while the results were quite different among studies. 2,23,36,47 Li et al 23 found that the SNQ value was positively correlated with age and TAS and negatively correlated with follow–up time and ACL graft–Blumensaat line angle in a stepwise regression analysis of 104 male patients with autograft or allograft ACLR. Okutan et al 36 evaluated 94 patients with hamstring autograft ACLR and concluded that the lateral tibial slope, remnant preservation, and graft–notch volume ratio were independently associated factors of graft SNQ.…”
Section: Discussionmentioning
confidence: 99%
“…2,23,36,47 Li et al 23 found that the SNQ value was positively correlated with age and TAS and negatively correlated with follow–up time and ACL graft–Blumensaat line angle in a stepwise regression analysis of 104 male patients with autograft or allograft ACLR. Okutan et al 36 evaluated 94 patients with hamstring autograft ACLR and concluded that the lateral tibial slope, remnant preservation, and graft–notch volume ratio were independently associated factors of graft SNQ. However, most previous studies analyzed the overall SNQ value while ignoring the variation along the graft route.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most possible reason is related to the mechanical effect of remnant tissue that limits the flow of synovial fluid into the tibial tunnel by covering the tunnel aperture. 20,21,26 Several studies have reported that synovial fluid contains high levels of inflammatory cytokines that inhibit bone formation, and it tends to propagate into the tibial tunnel under the effects of gravity. 11,31 Also, Sun et al 25 showed that the preservation of remnant tissue decreased fluid leakage into the tibial tunnel.…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 99%